2002
DOI: 10.4049/jimmunol.168.3.1479
|View full text |Cite
|
Sign up to set email alerts
|

The Role of T Cell Help in the Production of Antibodies Specific for Galα1–3Gal

Abstract: The majority of xenoreactive natural Abs in humans recognize the carbohydrate Ag present on pig tissue, Galα1–3Galβ1–4GlcNAc-R (αGal), synthesized by the enzyme UDP galactose:β-d-galactosyl-1,4-N-acetyl-d-glucosaminide α(1–3)galactosyltransferase or αGT. Using αGT knockout mice (GT0 mice), which like humans produce serum Abs that bind αGal, we examined the role of T cells in production of Abs specific for αGal. GT0 mice were crossed with TCR-β knockout mice (TCR-β0) to generate double-knockout mice (GT0/TCR-β0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 30 publications
5
57
2
Order By: Relevance
“…However, we previously showed that the MLN was not a major site for the production of either anti-Gal or total IgM Ab after rabbit RBC immunization i.p (13). Although evidence suggests that induced anti-Gal IgM Ab responses are largely T cell dependent in Gal knockout mice (36), this response appears to be dependent on the ␣␤ TCR-bearing class of T cells (37) and not on ␥␦ T cells (A. Thall, unpublished observations). Baseline anti-Gal IgM levels in Gal knockout mice are not fully dependent on T cells (A. Thall, unpublished observations), and T cell depletion seems to actually increase the baseline anti-Gal NAb levels (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, we previously showed that the MLN was not a major site for the production of either anti-Gal or total IgM Ab after rabbit RBC immunization i.p (13). Although evidence suggests that induced anti-Gal IgM Ab responses are largely T cell dependent in Gal knockout mice (36), this response appears to be dependent on the ␣␤ TCR-bearing class of T cells (37) and not on ␥␦ T cells (A. Thall, unpublished observations). Baseline anti-Gal IgM levels in Gal knockout mice are not fully dependent on T cells (A. Thall, unpublished observations), and T cell depletion seems to actually increase the baseline anti-Gal NAb levels (38).…”
Section: Discussionmentioning
confidence: 99%
“…52,53 However, we observed similar frequencies of cells with anti-␣Gal receptors in GalT Ϫ/Ϫ Cr2 Ϫ/Ϫ compared with GalT Ϫ/Ϫ mice, and the same B-1b-cell population appeared to be responsible for anti-␣Gal production in both groups. The relationship between B-1a and B-1b cells has not been well defined.Although there is some controversy regarding NAb regulation by T cells, 54 we have observed that baseline anti-␣Gal NAb levels are increased by depletion of T cells. 55 In contrast, the induced anti-␣Gal IgM response is largely T-cell dependent.…”
mentioning
confidence: 78%
“…55 In contrast, the induced anti-␣Gal IgM response is largely T-cell dependent. 54,56 Both baseline and induced anti-␣Gal levels were enhanced by nonhematopoietic CR1/CR2 expression, suggesting a role for FDC CR1/CR2 expression in both T-independent and T-dependent Ab responses.Total serum IgM levels were unaffected by the presence or absence of CR1/CR2 on hematopoietic and/or nonhematopoietic cells in our model. Our previous studies showing that anti-␣Gal-and total IgM-producing cells belong to the same B-cell subset 9 led to the expectation that total IgM levels would be reduced in mice lacking nonhematopoietic cell CR1/CR2 expression.…”
mentioning
confidence: 96%
“…To determine the extent to which a preformed immune response was a barrier to the induction of molecular chimerism, aGT knockout mice were immunized with aGal-expressing pig cells. Since aGal is a T-dependent antigen 28 this immunization resulted in T-cell priming and increased titers of antiGal antibodies. Despite high titers of serum aGal-specific antibodies in immunized hosts, molecular chimerism could be established by increasing the dose of transduced bone marrow used for reconstitution of lethally irradiated recipient.…”
Section: Induction Of Tolerance In Sensitized Recipientsmentioning
confidence: 99%